Modifications of Capsaicin-Sensitive Neurons in Isolated Guinea Pig Ileum by [6]-Gingerol and Lafutidine - Akiyoshi Someya; Shunji Horie; Hisashi Yamamoto; Toshihiko Murayama (Elsevier, 2003)
A segment of guinea pig ileum was used to confirm the hypothesis that [6]-gingerol and lafutidine interact with capsaicin-sensitive neurons. Addition of 30 and 100 μM [6]-gingerol (a pungent constituent of ginger) induced contraction of the ileum immediately. Like capsaicin, [6]-gingerol-induced contraction was inhibited by antagonists of the vanilloid receptor (capsazepine and ruthenium red), tetrodotoxin, and atropine. Treatment with [6]-gingerol up to 0.3 μM, which alone had no effect, enhanced 3 μM capsaicin-induced contraction, but greater than 3 μM [6]-gingerol significantly inhibited capsaicin-induced contraction. Treatment with lafutidine (a new type of antagonist of the histamine H2 receptor), which was suggested to interact with capsaicin-sensitive neurons in vivo, also showed both stimulatory and inhibitory effects on capsaicin-induced contraction depending on the concentrations. Lafutidine alone had no effect. The enhanced contraction induced by capsaicin in the [6]-gingerol- or lafutidine-treated ileum was also inhibited by antagonists of the vanilloid receptor, tetrodotoxin, and atropine. Capsaicin and [6]-gingerol, but not lafutidine, at 30 μM stimulated [3H]choline release from the prelabeled slices of the ileum. These findings suggest that [6]-gingerol and lafutidine act on capsaicin-sensitive cholinergic neurons and modulate the contraction in isolated guinea pig ileum.